Educational projects in Turkey as an instrument of «Soft» policy (Journal of history, 2022)
The previous century began with the First World War and ended with the end of the Cold War. In contrast to forceful actions, the concept of soft power has come into use. Unlike hard power, soft power did not use coercion. It was implemented through public diplomacy. This method was used by countries to clarify their political goals and strengthen friendly ties. Public diplomacy, carried out on the basis of cultural commonality, allowed countries to build their political courses. The primarily element of public diplomacy is two-way communication with the public, and the participants in the dialogue could be not only the government and the public, but also the general public with the general public. Student and teacher exchange programs, as part of higher education’s internationalization, are an important part of this communication. This was especially true for Turkey in the post-colonial era, given the development of new Turkicspeaking countries on the global scene. These events, together with Turkey’s geographic placement between Europe and Asia, will accelerate the development of diverse international educational programs. This not only allowed for the restoration of lost cultural links with Turkic countries, but also improved Turkey’s international image. Projects like the Great Student Project, Turkey Scholarships, and the Mevlana exchange program are discussed as soft power instruments in this article. The impact of events in Turkish foreign policy in the twenty-first century on the establishment of academic exchange programs will also be examined. Key words: soft power, education, exchange programs, Mevlana